¿Modelos unitarios o colectivos?: Perspectivas teóricas y evidencias preliminares provenientes de Perú - Monge Zegarra, Álvaro (2004)
The document provides so me theoretical insights around collective models of household decision making and resource allocation. These models, in contrast with unitary ones, consider the consumption decisions of the family to be a result of a bargaining process and interaction between household members. The predicted equilibrium conditions tend to differ from the traditional approach of utility maximization. The focus is centered on two specific issues: the emergence ofthe pooling income hypothesis (which characterizes unitary models) and the efficiency hypothesis (which characterizes, within the collective framework, cooperative solutions). Using these insights, the article establishes preliminary tests for the collective approach, as against the unitary one, using data for Peru, and then investigates whether efficiency is achieved in consumption allocation. The results presented provide new insights about consumption behavior in Peru.